Faktor yang Berhubungan dengan Kejadian Keputihan pada Remaja Putri di SMP Qur’an Eltahfidh Tahun 2025 - Putri Yuliana Lubis; Rosi Kurnia Sugiharti; Musmudiroh Musmudiroh; Triseu Setianingsih (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Vaginal discharge is a common reproductive health issue among adolescent girls, potentially affecting daily activities and psychosocial well-being. WHO (2021) reported that 75% of women have experienced vaginal discharge, with 45% experiencing it more than twice. In Indonesia, the prevalence reaches 90%, with about 60% occurring among adolescents. A preliminary survey at El Tahfidh Qur’an Junior High School found that 21.5% of female students experienced vaginal discharge, yet most could not distinguish between physiological and pathological discharge. This study aimed to analyze factors associated with the incidence of vaginal discharge among eighth and ninth-grade students at El Tahfidh Qur’an Junior High School in 2025. This quantitative study employed a cross-sectional design involving 93 respondents selected through total sampling. Data were collected using a questionnaire and analyzed using the Chi-Square test and Odds Ratio (OR). Results showed significant associations between knowledge (p=0.000; OR=7.875), age (p=0.001; OR=0.257), personal hygiene (p=0.000; OR=7.286), and information sources (p=0.007; OR=0.295) and the incidence of vaginal discharge. It can be concluded that improving knowledge, practicing proper personal hygiene, and obtaining valid health information play crucial roles in preventing vaginal discharge among adolescent girls.